2004
DOI: 10.1038/sj.onc.1207751
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cancer

Abstract: Large prospective studies show a significant association with obesity for several cancers, and the International Agency for Research on Cancer has classified the evidence of a causal link as 'sufficient' for cancers of the colon, female breast (postmenopausal), endometrium, kidney (renal cell), and esophagus (adenocarcinoma). These data, and the rising worldwide trend in obesity, suggest that overeating may be the largest avoidable cause of cancer in nonsmokers. Few obese people are successful in long-term wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
356
2
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 615 publications
(380 citation statements)
references
References 135 publications
2
356
2
13
Order By: Relevance
“…obstructive sleep apnoea and asthma), and neoplasia (e.g. breast, prostatic, ovarian, colonic/rectal, renal cell and oesophageal cancer (2)(3)(4)(5) . Not surprisingly, obesity conveys increased risk of mortality to affected human subjects (6) .…”
Section: The Significance Of Obesity In Petsmentioning
confidence: 99%
“…obstructive sleep apnoea and asthma), and neoplasia (e.g. breast, prostatic, ovarian, colonic/rectal, renal cell and oesophageal cancer (2)(3)(4)(5) . Not surprisingly, obesity conveys increased risk of mortality to affected human subjects (6) .…”
Section: The Significance Of Obesity In Petsmentioning
confidence: 99%
“…It is likely that the relationship between body composition and morbidity is multifactorial. Lifestyle, diet and genetic factors probably contribute to the adverse health effects of obesity, and fat tissue may theoretically act as a storage reservoir for toxins that could contribute to the pro-carcinogenic effects of obesity (Calle and Thun, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the Family Budget Survey, carried out between 2008 and 2009, showed that in Brazil obesity affects approximately 14 % of adults over the age of 20 years (2) . Obesity is linked to many adverse health outcomes, including diabetes, CVD, cancer and overall mortality (3)(4)(5)(6) . Traditionally, causes of obesity have been linked to the imbalance between energy intake and physical activity (7) .…”
mentioning
confidence: 99%